Technologies of sustainable development : selected peer-reviewed full text papers from the 3rd Borneo International Conference on Applied Mathematics and Engineering (3rd BICAME) - Laksono, Andromeda Dwi (Trans Tech Publications, 2021)
Selected peer-reviewed full text papers from the 3rd Borneo International Conference on Applied Mathematics and Engineering (3rd BICAME) Selected, peer-reviewed papers from the 3rd Borneo International Conference on Applied Mathematics and Engineering 2020 (3rd BICAME 2020), September 9-10, 2020, Balikpapan, Indonesia.
Description based upon print version of record.
Keywords: Applied mathematics -- Congresses.; Applied mathematics; Sustainable development -- Mathematics -- Congresses.; Environmental engineering -- Congresses.; elektronické knihy; electronic books